2007
DOI: 10.1002/term.15
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering: chondrocyte culture on type 1 collagen support. Cytohistological and immunohistochemical study

Abstract: The scope of our study is to evaluate the possibility of cultivating and expanding human chondrocytes and seeding them on pure equine type I collagen support. Our results show that human articular cartilaginous cells can multiply and grow on type I collagen substrate with production of extracellular matrix. This type of chondrocyte culture on a support can be used for repairing cartilaginous lesions since they show a correct morphology (evaluated by cytological and histological methods) and a suitable differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Yasui et al [8] previously observed that the chondrocytes proliferated and maintained their cartilage phenotype in type I collagen gel. Negri et al [9] also demonstrated that human chondrocytes were capable of multiplying in type I collagen to present cartilage ECM. We fabricated previously alginate-hyaluronic acid based hydrogel with the incorporation of type I collagen [10].…”
Section: Introductionmentioning
confidence: 97%
“…Yasui et al [8] previously observed that the chondrocytes proliferated and maintained their cartilage phenotype in type I collagen gel. Negri et al [9] also demonstrated that human chondrocytes were capable of multiplying in type I collagen to present cartilage ECM. We fabricated previously alginate-hyaluronic acid based hydrogel with the incorporation of type I collagen [10].…”
Section: Introductionmentioning
confidence: 97%
“…6,7 These results indicate that chondrogenic differentiation is strongly supported by the embedding of the chondrocytes in 3D carrier systems. [8][9][10] This 3D culture is considered to be preferable to direct re-injection of the isolated chondrocytes without further cultivation, because it favours adaptation of the cells to the final scaffold/matrix conditions and the beginning of the formation of an extracellular matrix.…”
mentioning
confidence: 99%
“…Because cell phenotype and extracellular matrix (ECM) vary with cartilage depth 9 , constructs, once implanted, are influenced by the native cell metabolism of each zone 10 .…”
Section: Discussionmentioning
confidence: 99%